Wikipedia as an arena and source for the public: a scandinavian comparison of “Islam” - Moe, Hallvard (Javnost-The Public, 2019)
This article compares Wikipedia as an arena and source for the public through analysis of articles on “Islam” across the three Scandinavian languages. Findings show that the Swedish article is continuously revised and adjusted by a fairly high number of contributors, with comparatively low concentration to a small group of top users. The Norwegian article is static, more basic, but still serves as a matter-of-factly presentation of Islam as religion to a stable amount of views. In contrast, the Danish article is at once more dynamic through more changes up until recently, it portrays Islam differently with a distinct focus on identity issues, and it is read less often. The analysis illustrates how studying Wikipedia can bring light to the receiving end of what goes on in the public sphere. The analysis also illustrates how our understanding of the online realm profits from “groundedness,” and how the comparison of similar sites in different languages can yield insights into cultural as well as political differences, and their implications.